2016
DOI: 10.2140/apde.2016.9.487
|View full text |Cite
|
Sign up to set email alerts
|

Nontransversal intersection of free and fixed boundaries for fully nonlinear elliptic operators in two dimensions

Abstract: In the study of classical obstacle problems, it is well known that in many configurations the free boundary intersects the fixed boundary tangentially. The arguments involved in producing results of this type rely on the linear structure of the operator. In this paper we employ a different approach and prove tangential touch of free and fixed boundary in two dimensions for fully nonlinear elliptic operators. Along the way, several n-dimensional results of independent interest are obtained such as BMOestimates,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…u 0 . It follows that @ x 1 u 0 .´/ D M´n and proceeding as in [17], one deduces that u 0 .x/ D ax 1 x n C z bx 2 n for a ¤ 0 and z b 2 R (up to a translation along the x 1 -axis), contradicting that u 0.…”
Section: Regularitymentioning
confidence: 93%
See 3 more Smart Citations
“…u 0 . It follows that @ x 1 u 0 .´/ D M´n and proceeding as in [17], one deduces that u 0 .x/ D ax 1 x n C z bx 2 n for a ¤ 0 and z b 2 R (up to a translation along the x 1 -axis), contradicting that u 0.…”
Section: Regularitymentioning
confidence: 93%
“…In [17] it was shown that W 2;p -solutions are C 1;1 . Furthermore, given u 2 P C r .0; M; /, the free boundary is denoted by…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…We consider the L 2 projection of D 2 u on the space of Hessians generated by second order homogeneous harmonic polynomials on balls with radius r > 0 and show that the projections stay uniformly bounded as r → 0 + . Although this approach has proven effective in dealing with a variety of free boundary problems [2,6,8,9], Theorem 1.1 illustrates that it is also useful in extending and refining the classical elliptic theory.…”
Section: The Classical Theorymentioning
confidence: 99%